Socio-Digital Transformations in Malayalam Language Practice, Pedagogical Renewal, and Identity Formation - Mohammed, Musthaqeem (Modality Journal: International Journal of Linguistics and Literature, 2025)
This interdisciplinary study examines the socio-digital evolution of Malayalam a major Dravidian language spoken primarily in Kerala and its diaspora within the context of globalization in the twenty-first century. Employing a combination of qualitative methodologies, including a comprehensive literature review, discourse analysis of digital Malayalam media, and ethnographic interviews, the research delves into the dynamic interaction between tradition and technological advancements. By investigating case studies on AI-driven speech synthesis technologies, government-led digital inclusion initiatives, and diaspora-driven cultural activism, the study reveals the adaptive strategies employed by the language community. This research's novelty lies in its interdisciplinary approach, merging sociolinguistic, pedagogical, and digital media perspectives to understand Malayalam’s contemporary transformations. The findings underscore the critical role of digital platforms in facilitating language use and fostering community engagement, while also emphasizing the impact of innovative pedagogical strategies particularly those promoting immersive, contextualized learning in reinforcing learner agency and cultural continuity.